REVITALISASI IDEOLOGI PANCASILA DALAM MEMBENTUK KONSEP HUKUM YANG HUMANIS - Supriyono Supriyono; Intan Kusumawati (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
The human life that is in the globalization period has a lot of shifting values, and the norm that raises behaviors that tend to ignore norms and moral order. Pancasila as an open ideology continues to improve itself by developing meaning without compromising the basic value. The law in Indonesia contains rules to control the global values that have been present. Indonesian man is a culture that is obedient to the rules or the positive law by using progressive law that is sourced from the value of humanity. Pancasila as the foundation of the legal source will be the footing of the community to be a good citizen in the Order of society, nation and state that remains oriented to the human being itself. The research method of using the normative law reach is research with the approach of legislation. The results showed the revitalization of Pancasila ideology as an attempt to return Pancasila as a guideline for Indonesia's nation and state. Pancasila as a national ideology as a nation, advisers and directors in the country of Indonesia that is a charateristic nation.